POROUS RUTHENIUM OXIDE-BASED CATALYST INCORPORATED WITH d0 METAL IONS FOR OXYGEN EVOLUTION REACTION, METHOD FOR PREPARING SAME, AND PROTON EXCHANGE MEMBRANE WATER ELECTROLYZER COMPRISING SAME

KR103019299B1Active Publication Date: 2026-09-15KOREA ADVANCED INST OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020250081637
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2026-09-15
Estimated Expiration
2045-06-20

Smart Images

  • Figure 112025069221944-PAT00003_ABST
    Figure 112025069221944-PAT00003_ABST
Patent Text Reader

Abstract

One embodiment of the present invention provides a catalyst for an oxygen evolution reaction in which a metal ion having a d0 electron configuration is introduced into a ruthenium oxide (RuO2) matrix. The introduction of the metal ion effectively controls the O 2p band center and Ru-O covalent bonding of the ruthenium oxide, thereby inducing the oxygen evolution reaction mechanism to a lattice oxygen-mediated mechanism (LOM). Through this, the catalyst exhibits excellent electrochemical activity and enhanced durability even in an acidic electrolyte environment, which can significantly improve the performance of a proton exchange membrane water electrolysis (PEMWE).
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a catalyst for an oxygen evolution reaction, a method for manufacturing the same, and an electrochemical water splitting device including the same. More specifically, the invention relates to a catalyst having a porous structure in which d0 metal ions are introduced into ruthenium oxide to activate a lattice oxygen-mediated mechanism (LOM) and exhibit excellent oxygen evolution activity and durability, a method for efficiently manufacturing the catalyst, and a proton exchange membrane water electrolysis device with enhanced energy efficiency and long-term stability by applying the catalyst to an anode. Background Technology

[0003] With the advancement of energy conversion and storage technologies, the Oxygen Evolution Reaction (OER) plays a key role in eco-friendly energy systems, such as hydrogen production through water electrolysis or chemical fuel production through carbon dioxide reduction. In particular, Proton Exchange Membrane Water Electrolysis (PEMWE) devices are attracting attention for their ability to produce high-purity hydrogen with high energy efficiency and current density; however, due to the acidic operating environment, the use of precious metal-based electrocatalysts, such as platinum (Pt) or iridium (Ir), is essential.

[0004] The oxygen evolution reaction requires an overpotential much higher than the theoretical potential due to complex multi-electron transfer processes and slow reaction rates, which is a major cause of reduced energy efficiency in the overall system. In particular, the oxygen evolution reaction occurring at the anode determines the rate of the overall water electrolysis reaction, and iridium oxide (IrO₂)-based catalysts are primarily used in current commercial PEMWE. However, iridium has limited reserves and is very expensive, posing a significant obstacle to the widespread adoption of PEMWE technology. Therefore, there is an urgent need to develop inexpensive yet efficient catalysts for the oxygen evolution reaction that can reduce iridium usage or replace it.

[0005] The oxygen evolution reaction mechanism is mainly divided into the Adsorbate Evolution Mechanism (AEM) and the Lattice Oxygen-mediated Mechanism (LOM). The traditional AEM is a mechanism in which water molecules adsorbed to metal active sites on the catalyst surface undergo a sequential oxidation process to form oxygen molecules. It is known that there is a theoretical limit (approx. 370 ± 100 mV) to lowering the overpotential due to the linear scaling relationship of adsorption energies between reaction intermediates (*OH, *O, *OOH).

[0006] To overcome the limitations of AEM, LOM has been proposed as an alternative. LOM is a mechanism in which oxygen within the catalyst lattice directly participates in the oxygen evolution reaction to form OO bonds; by bypassing *OOH intermediates, it overcomes the constraints of linear relationships and possesses the potential to exhibit higher activity. In fact, LOM-dominant catalysts have been reported to show superior oxygen evolution activity compared to AEM-based catalysts. Ruthenium oxide (RuO₂) is a representative material capable of exhibiting LOM activity; while it has superior initial activity compared to iridium oxide, its low durability in acidic environments is pointed out as a major problem.

[0007] In the case of LOM-based catalysts, particularly RuO₂, oxygen vacancies generated as lattice oxygen participates in the reaction cause structural instability in the catalyst. These oxygen vacancies promote the leaching of surface Ru or induce Ru peroxidation, ultimately leading to rapid deactivation of the catalyst as RuO₄ is lost. Consequently, RuO₂ with high crystallinity and suppressed LOM activity tends to have higher stability but lower activity than RuO₂ with low crystallinity and many defects, making it difficult to utilize the advantages of LOM in acidic PEMWE environments.

[0008] Due to these issues, much existing research has focused on ensuring durability by intentionally suppressing the LOM activity of Ru-based catalysts and inducing them to follow AEM. However, this approach falls short of being a fundamental solution as it sacrifices the benefits of high intrinsic activity that LOM can provide. Therefore, there is an urgent need to develop new catalyst design strategies that can maintain high LOM activity even in acidic environments while simultaneously securing excellent durability through the stabilization of oxygen vacancies. The problem to be solved

[0010] The present invention has been devised to solve the aforementioned problems, and one embodiment of the present invention provides a catalyst for an oxygen generation reaction.

[0011] In addition, another embodiment of the present invention provides a method for manufacturing a catalyst for an oxygen evolution reaction.

[0012] In addition, another embodiment of the present invention provides a proton exchange membrane water electrolysis device.

[0013] The technical problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned technical problems will be clearly understood by those skilled in the art to which the present invention belongs from the description below. means of solving the problem

[0015] As a technical means for achieving the aforementioned technical problem, one aspect of the present invention is,

[0016] A catalyst for an oxygen evolution reaction is provided, comprising: a porous structure comprising ruthenium oxide (RuO2), wherein a plurality of ruthenium oxide primary particles aggregate to form secondary particles and include interparticle pores between the primary particles; and one or more metal ions having a d0 electron configuration dispersed on the surface or inside the pores of the porous structure.

[0017] The metal ion having the above d0 electronic configuration may be one or more selected from the group consisting of Y (yttrium), Gd (gadolinium), and La (lanthanum).

[0018] H₂ 18 As a result of digitally labeled mass spectrometry (DEMS) in a 0.5 M H₂SO₄ electrolyte containing O, the oxygen evolution reaction (OER) participation rate of lattice oxygen can be 30% or more.

[0019] In the O 1s spectrum measured by X-ray photoelectron spectroscopy (XPS), the area ratio of oxygen vacancies (OV) to lattice oxygen (OL) (OV / OL) can be 1.9 or higher.

[0020] The specific surface area measured by the BET (Brunauer-Emmett-Teller) method is 40 m² 2 g -1 to 70 m 2 g -1 It could be.

[0021] 10 mA cm⁻¹ in 0.5 M H₂SO₄ electrolyte -2 When operated for 10 hours at a current density, the amount of Ru leached into the electrolyte may be 2.5 μg or less.

[0022] The energy difference between the Ru 4d band center and the O 2p band center based on density functional theory (DFT) calculations can be 1.8 eV or less.

[0023] The center of the O 2p band based on density functional theory (DFT) calculations can be greater than -3.4 eV.

[0024] 10 mA cm⁻¹ in 0.5 M H₂SO₄ electrolyte -2 The overvoltage required to achieve the current density can be 250 mV or less.

[0025] The Tafel slope measured in 0.5 M H₂SO₄ electrolyte was 40 mV dec -1 It may be less than.

[0027] Another aspect of the present invention is,

[0028] The present invention provides a method for manufacturing a catalyst for an oxygen evolution reaction, comprising the steps of: preparing a zeolitic imidazolate framework (ZIF) template; contacting the ZIF template with an aqueous solution containing ruthenium ions and metal ions having a d0 electron configuration so that the ZIF template is gradually etched and simultaneously ruthenium and d0 metal precursors are formed; and heat-treating the ZIF template formed with the ruthenium and d0 metal precursors in air to obtain a ruthenium oxide catalyst having a porous structure according to claim 1 into which the d0 metal ions are introduced.

[0029] The above ZIF mold may be ZIF-8.

[0030] The precursor of the metal ion having the above d0 electronic configuration may be in the form of nitrate or chloride.

[0031] The above heat treatment step can be performed in a temperature range of 300 °C to 400 °C.

[0032] The aqueous solution in the step of contacting the above ZIF template with an aqueous solution containing ruthenium ions and metal ions having a d0 electron configuration so that the ZIF template is gradually etched and simultaneously ruthenium and d0 metal precursors are formed may include ruthenium chloride (RuCl₃·xH₂O) and one or more d0 metal salts selected from Y(NO₃)₂·6H₂O, Ce(NO₃)₂·6H₂O, La(NO₃)₂·6H₂O, or Gd(NO₃)₂·6H₂O.

[0034] Another aspect of the present invention is,

[0035] The present invention provides a proton exchange membrane water electrolysis device comprising an anode; a cathode; and a proton exchange membrane disposed between the anode and the cathode, wherein the anode comprises the catalyst.

[0036] The catalyst loading amount at the above anode is 2.0 mgcat cm⁻¹ -2 Up to 4.0 mg cat cm -2 It can be a range.

[0037] It may be operated at an operating temperature of 80 °C to 100 °C.

[0038] 1.0 A cm at a cell voltage of 1.6 V -2 It may indicate a current density above.

[0039] 200 mA cm -2 When operating for 100 hours at a current density, the cell voltage rise can be 20 mV or less. Effects of the invention

[0041] According to an embodiment of the present invention, by introducing d0 metal ions into ruthenium oxide to effectively activate the lattice oxygen-mediated mechanism (LOM), the catalytic activity for the oxygen evolution reaction (OER) in an acidic electrolyte and long-term durability can be significantly improved simultaneously.

[0042] In addition, according to one embodiment of the present invention, by applying the catalyst to the anode of a proton exchange membrane water electrolysis device, superior hydrogen production performance and long-term operational stability compared to existing commercial catalysts are achieved, thereby contributing to the realization of a high-efficiency and high-durability water electrolysis system.

[0043] The effects of the present invention are not limited to the effects described above, and should be understood to include all effects that can be inferred from the composition of the invention described in the description or claims of the present invention. Brief explanation of the drawing

[0045] FIG. 1 is a schematic diagram showing the adsorbate evolution mechanism (AEM) and lattice oxygen-mediated mechanism (LOM) pathways in an oxygen evolution reaction according to one embodiment of the present invention, and the band diagram change for the anion redox activation of lattice oxygen. FIG. 2 is a diagram showing a transmission electron microscope (TEM) image of a ZIF-8 template used in the synthesis of an M-RuO₂ electrocatalyst according to one embodiment of the present invention. FIG. 3 is a diagram showing the synthesis process of an M-RuO₂ electrocatalyst according to one embodiment of the present invention, a high-angle annular dark-field scanning transmission electron microscope (HAADF-STEM) image of Y-RuO₂, and the energy-dispersive X-ray spectroscopy (EDS) elemental mapping results. FIG. 4 is a diagram showing the HAADF-STEM image and EDS elemental mapping results of RuO₂ according to one embodiment of the present invention. FIG. 5 is a diagram showing the HAADF-STEM image and EDS elemental mapping results of Ce-RuO₂ according to one embodiment of the present invention. FIG. 6 is a diagram showing the HAADF-STEM image and EDS elemental mapping results of Gd-RuO₂ according to one embodiment of the present invention. FIG. 7 is a diagram showing the HAADF-STEM image and EDS elemental mapping results of La-RuO₂ according to one embodiment of the present invention. FIG. 8 is a diagram showing the nitrogen adsorption-desorption isotherm and the Barrett-Joyner-Halenda (BJH) pore size distribution curve of M-RuO₂ according to one embodiment of the present invention. FIG. 9 is a diagram showing the X-ray diffraction (XRD) pattern of an M-RuO₂ electrocatalyst according to one embodiment of the present invention, the O 1s X-ray photoelectron spectroscopy (XPS) spectrum of Y-RuO₂, the OV / OL ratio, the Ru 3d XPS spectrum of M-RuO₂, the Ru K-edge X-ray absorption near-layer structure (XANES) spectrum, and the extended X-ray absorption fine structure (EXAFS) spectrum. FIG. 10 is a figure showing high-resolution O 1s XPS spectra of RuO₂, Ce-RuO₂, Gd-RuO₂ and La-RuO₂ according to one embodiment of the present invention. FIG. 11 is a figure showing the Y 3d, Ce 3d, Gd 4d, and La 3d high-resolution XPS spectra of M-RuO₂ according to one embodiment of the present invention. FIG. 12 is a graph showing the correlation between the XANES end energy and the Ru oxidation state according to one embodiment of the present invention. FIG. 13 is a cyclic voltammetry curve of an M-RuO₂ electrocatalyst according to one embodiment of the present invention, 10 mA cm⁻¹ -2 This is a diagram showing the overpotential, Tafel plot, potential change over time, and differential electrochemical mass spectrometry (DEMS) signals of RuO₂ and Y-RuO₂. FIG. 14 is a graph showing the mass activity curve of electrocatalysts according to one embodiment of the present invention and the mass activity at 1.45 V. FIG. 15 is a diagram showing cyclic voltammetry curves for measuring electrochemical double layer capacitance of M-RuO₂ and c-RuO₂ at various scan rates according to one embodiment of the present invention. FIG. 16 is a figure showing a double-layer charging current density curve according to a scan rate and an oxygen evolution reaction (OER) inactive curve normalized by the electrochemical active surface area (ECSA) according to an embodiment of the present invention. FIG. 17 shows the Ru K-edge XANES spectra and k before and after the OER test of RuO₂ and Y-RuO₂ according to one embodiment of the present invention. 2 - This is a diagram showing the weighted Fourier transform EXAFS spectrum. FIG. 18 is a diagram showing DEMS signals collected during a cyclic voltammetry (CV) cycle of c-RuO₂ according to one embodiment of the present invention. FIG. 19 shows 0.5 M H₂SO₄ and 0.01 M TMA according to one embodiment of the present invention. + This is a diagram showing the average CV curves of the forward and reverse scans tested in the electrolyte. FIG. 20 is a diagram showing the surface structure of RuO₂ (110) and Y-RuO₂ (110) model catalysts used in DFT calculations according to one embodiment of the present invention. FIG. 21 is a diagram of the results of density functional theory (DFT) calculations showing the OER free energy change for the AEM and LOM paths on RuO₂ (110) and Y-RuO₂ (110) surfaces according to one embodiment of the present invention, the projected density of states (PDOS) of these surfaces, and the correlation between experimental overpotential and the catalytic surface electronic structure index. FIG. 22 is a diagram showing the DFT optimized structure of an OER reaction intermediate for RuO₂ (110) and Y-doped RuO₂ (110) according to one embodiment of the present invention. FIG. 23 is a diagram showing the single-cell polarization curve, corresponding Tafel plot, overpotential analysis results, and long-term durability test results of a proton exchange membrane water electrolysis (PEMWE) using commercial RuO₂ or Y-RuO₂ as an anode catalyst according to one embodiment of the present invention. Specific details for implementing the invention

[0046] The present invention will be described in more detail below. However, the present invention may be implemented in various different forms and is not limited by the embodiments described herein, and is defined only by the claims set forth below.

[0047] Additionally, the terms used in this invention are used merely to describe specific embodiments and are not intended to limit the invention. Singular expressions include plural expressions unless the context clearly indicates otherwise. Throughout the specification of this invention, the term 'comprising' any component means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.

[0048] Throughout the specification, when it is stated that a part is "connected (connected, in contact, combined)" with another part, this includes not only cases where they are "directly connected," but also cases where they are "indirectly connected" with other members in between. Furthermore, when it is stated that a part "includes" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but rather allows for the inclusion of additional components.

[0049] Unless otherwise noted, “%” used in the specification may mean “weight%” or “wt%” regarding content.

[0050] The terms used in this specification are used merely to describe specific embodiments and are not intended to limit the invention. The singular expression includes the plural expression unless the context clearly indicates otherwise.

[0052] The first aspect of the present invention is,

[0053] A catalyst for an oxygen evolution reaction is provided, comprising: a porous structure comprising ruthenium oxide (RuO2), wherein a plurality of ruthenium oxide primary particles aggregate to form secondary particles and include interparticle pores between the primary particles; and one or more metal ions having a d0 electron configuration dispersed on the surface or inside the pores of the porous structure.

[0055] Hereinafter, a catalyst for an oxygen generation reaction according to the first aspect of the present invention will be described in detail.

[0057] In one embodiment of the present invention, the ruthenium oxide acts as a major matrix material having intrinsic catalytic activity for the oxygen evolution reaction, and during the synthesis process, nanometer-sized primary particles tend to aggregate to form secondary particles of several hundred nanometers in size. Within these secondary particles, numerous interparticle pores formed between the primary particles exist, which can provide a large specific surface area and improve the accessibility of reactants. Consequently, this hierarchical porous structure contributes to the overall electrochemical performance of the catalyst.

[0058] In one embodiment of the present invention, the average diameter of the primary ruthenium oxide particles constituting the catalyst may be in the range of 5 nm or 8 nm to 15 nm or 20 nm, and the average diameter of the secondary particles formed by the aggregation of these primary particles may be in the range of 50 nm or 100 nm to 300 nm or 500 nm. If the particle size is below the above-described range, the structural instability of the catalyst may increase, or it may be difficult to form an effective pore structure within the secondary particles, which may lead to a decrease in activity. On the other hand, if the particle size exceeds the above-described range, the overall catalyst efficiency may decrease due to a decrease in the utilization rate of the catalyst active sites and an increase in the mass transfer resistance of the reactants / products.

[0059] In one embodiment of the present invention, the metal ion having the d0 electron configuration may be a rare earth metal ion such as yttrium (Y), cerium (Ce), gadolinium (Gd), or lanthanum (La), and preferably, it may be one or more selected from the group consisting of Y, Gd, and La, which have excellent effects in improving oxygen evolution reaction (OER) activity and durability. The introduction of such d0 metal ions can play a key role in promoting the lattice oxygen-mediated mechanism (LOM) by controlling the O 2p band center and Ru-O covalent bonding of ruthenium oxide, thereby simultaneously enhancing the oxygen evolution reaction activity and structural stability (particularly contributing to oxygen vacancy stabilization) of the catalyst.

[0060] In one embodiment of the present invention, the specific surface area measured by the BET (Brunauer-Emmett-Teller) method is as wide as 30 m² 2 g -1 to 80 m 2 g -1 The range of, or 35 m 2 g -1 to 75 m 2 g -1 The range of, or more preferably 40 m 2 g -1 to 70 m 2 g -1 The range of, or more preferably 45 m 2 g -1 to 65 m 2 g -1 It may be within the range. If it is below the aforementioned desirable range, the effective active area of ​​the catalyst is not sufficiently secured, and mass transfer characteristics are degraded, which may result in a lower overall oxygen generation efficiency. On the other hand, if it exceeds the aforementioned desirable range, it may instead cause problems such as reduced stability of catalyst particles or low packing density within the electrode layer without any particular additional performance improvement.

[0061] In one embodiment of the present invention, the total pore volume of the catalyst is 0.10 cm when measured by nitrogen adsorption-desorption analysis. 3 g -1 or 0.12 cm 3 g -1 up to 0.22 cm 3 g -1 or 0.25 cm 3 g -1 It can be within a certain range. Such a sufficient pore volume can improve mass transfer efficiency by enabling the smooth supply of reactants to the catalytic active site and the effective discharge of generated gaseous products.

[0062] In one embodiment of the present invention, the average size of the pores formed within the catalyst may be a meso size in the range of 5 nm or 10 nm to 30 nm or 40 nm when analyzed by the BJH (Barrett-Joyner-Halenda) method. Pores of this size provide a large reaction surface area and simultaneously serve as pathways for reaction-related species, which can have a positive effect on the overall performance of the catalyst.

[0063] In one embodiment of the present invention, differential electrochemical mass spectrometry (DEMS) combined with isotope labeling experiments may be utilized to elucidate the oxygen evolution reaction (OER) mechanism. For example, oxygen within the catalyst lattice 16 Composed of O and H₂ 18 Oxygen gas generated while carrying out OER in an electrolyte environment containing O ( 32 O₂, 34 O₂, 36By analyzing the isotopic composition of O₂ using DEMS, it is possible to quantitatively evaluate the contribution of the Lattice Oxygen-Mechanized Mechanism (LOM), in which oxygen within the catalyst lattice directly participates in the reaction, and the contribution of the Adsorbate Evolution Mechanism (AEM), in which oxygen derived from water molecules in the electrolyte reacts. This provides important information for experimentally clarifying the impact of catalyst design strategies, such as the introduction of d0 metal ions, on the actual OER mechanism, and for understanding the fundamental causes of changes in catalytic activity.

[0064] A catalyst according to one embodiment of the present invention is H₂ 18 Based on the results of digitally labeled mass spectrometry (DEMS) in a 0.5 M H₂SO₄ electrolyte containing O, the participation rate of lattice oxygen in the oxygen evolution reaction (OER) may be 20% or more, 25% or more, 30% or more, or 35% or more as a lower limit, and 70% or less, 60% or less, 55% or less, or 50% or less as an upper limit. If the participation rate falls short of the aforementioned preferred range, the oxygen evolution reaction of the catalyst relies mainly on the adsorbate evolution mechanism (AEM), which limits the improvement of intrinsic activity due to constraints on linear relationships and may result in a higher overpotential. On the other hand, if the lattice oxygen participation rate excessively exceeds the aforementioned preferred range and the consumption of lattice oxygen is very rapid, it may be detrimental to long-term durability if the oxygen vacancy recovery and structural stabilization effects by d0 metal ions do not sufficiently support this.

[0065] In one embodiment of the present invention, X-ray photoelectron spectroscopy (XPS) may be utilized to analyze the surface oxygen state of the catalyst, and in particular, the high-resolution O 1s spectrum can be deconvolved into components generally associated with lattice oxygen (OL) near about 529.5 eV, oxygen vacancies (OV) or defect site oxygen near about 531 eV, and surface adsorbed water (H2Oad) near about 533 eV. The relative area ratio of these components, in particular the ratio of oxygen vacancies to lattice oxygen (OV / OL), can be used as an important indicator related to the degree of defects on the catalyst surface and the activability of lattice oxygen, and the present invention aims to improve oxygen evolution reaction (OER) characteristics by controlling this ratio through the introduction of d0 metal ions.

[0066] According to one embodiment of the present invention, the catalyst may have an area ratio of oxygen vacancies to lattice oxygen (OV / OL) based on the O 1s XPS spectrum analysis results, with a lower limit of 1.7 or higher, or 1.8 or higher, or 1.9 or higher, or 2.0 or higher, and an upper limit of 3.0 or lower, or 2.8 or lower, or 2.6 or lower, or 2.4 or lower. If the value is below the above-described preferred range, the concentration of oxygen vacancies formed and stabilized on the catalyst surface is insufficient, which inhibits the mobility of lattice oxygen and the activation of the lattice oxygen-mediated mechanism (LOM), and may result in low intrinsic OER activity of the catalyst. On the other hand, if the concentration of oxygen vacancies is excessively high by exceeding the above-described preferred range, it may cause severe instability of the catalyst lattice structure despite the stabilizing effect of d0 metal ions, making it difficult to ensure long-term durability.

[0067] In one embodiment of the present invention, the electronic structural characteristics of the catalyst can be analyzed through density functional theory (DFT) calculations, and in particular, the energy difference between the ruthenium (Ru) 4d band center and the oxygen (O) 2p band center is an important indicator of the covalency of the Ru-O bond. A smaller energy difference can be interpreted as strengthening the Ru-O covalency, which is understood to shift the O 2p band center near the Fermi level, thereby promoting the participation of lattice oxygen in redox reactions and consequently contributing to increased oxygen evolution (OER) activity through the lattice oxygen-mediated mechanism (LOM).

[0068] In one embodiment of the present invention, the electronic structure of the catalyst, particularly the position of the oxygen (O) 2p band center, is closely related to the activation of the lattice oxygen-mediated mechanism (LOM). Generally, as the O 2p band center shifts upward closer to the Fermi level (EF) (i.e., has a less negative value), the lattice oxygen species can more easily participate in redox reactions, thereby promoting the LOM, which can contribute to enhancing the intrinsic activity of the oxygen evolution reaction (OER). In one embodiment of the present invention, the OER performance may be optimized by effectively controlling this O 2p band center through the introduction of d0 metal ions.

[0069] In one embodiment of the present invention, the electronic structure of the catalyst, particularly the position of the ruthenium (Ru) 4d band center, is an important factor that determines the energy level relative to the oxygen (O) 2p band center and influences the covalent nature of the Ru-O bond. Generally, as the Ru 4d band center moves downward (i.e., has a more negative value), the energy difference with the O 2p band center decreases, which can strengthen the Ru-O covalent nature. This can be advantageous for promoting the lattice oxygen-mediated mechanism (LOM) and improving oxygen evolution reaction (OER) activity. In one embodiment of the present invention, OER performance may be improved by controlling the position of the Ru 4d band center through the introduction of d0 metal ions.

[0070] In one embodiment of the present invention, the O 2p band center calculated by density functional theory (DFT) may be, as a lower limit, for example, -3.7 eV or higher, or -3.6 eV or higher, or -3.5 eV or higher, or -3.4 eV or higher, or -3.3 eV or higher, and as an upper limit, for example, -2.5 eV or lower, or -2.8 eV or lower, or -3.0 eV or lower, or -3.1 eV or lower. If the O 2p band center is lower than the above-described preferred range (e.g., -3.4 eV or higher and -3.0 eV or lower) (if it has a more negative value), it is difficult for lattice oxygen to participate in the redox reaction, and thus the lattice oxygen-mediated mechanism (LOM) is not effectively activated, so the intrinsic activity of the oxygen evolution reaction is low and the overpotential may increase. On the other hand, if the center of the O 2p band is too close to the Fermi level or too high (e.g., above -2.5 eV), the stability of oxygen in the catalyst lattice is significantly reduced, causing spontaneous oxygen escape or structural collapse, which may make long-term use as a catalyst difficult.

[0071] In one embodiment of the present invention, the Ru 4d band center calculated by density functional theory (DFT) may be, for example, -2.5 eV or higher, or -2.3 eV or higher, or -2.1 eV or higher, or -2.0 eV or higher as a lower limit, and may be, for example, -1.0 eV or lower, or -1.3 eV or lower, or -1.5 eV or lower, or -1.7 eV or lower as an upper limit. If the Ru 4d band center is excessively lower than the above-described preferred range (e.g., -2.1 eV or higher and -1.5 eV or lower), it may cause excessive changes in the metal-oxygen bonding characteristics or instability in the electronic structure, which may have a negative effect on the stability or activity of the catalyst. On the other hand, if the Ru 4d band center is higher than the aforementioned desirable range (i.e., has a less negative value), the energy difference with the O 2p band center increases, weakening the Ru-O covalent bond and preventing sufficient activation of lattice oxygen, which may lead to a decrease in OER activity.

[0072] In one embodiment of the present invention, the energy difference between the Ru 4d band center and the O 2p band center calculated by the above DFT may be 1.0 eV or more, or 1.2 eV or more, or 1.3 eV or more, or 1.4 eV or more as a lower limit, and 2.0 eV or less, or 1.9 eV or less, or 1.8 eV or less, or 1.7 eV or less, or 1.6 eV or less as an upper limit. If the energy difference is large exceeding the above-described preferred range (e.g., 1.8 eV or less), the covalent bonding of the Ru-O bond is weakened and the O 2p band center cannot effectively rise, making it difficult for lattice oxygen to participate in the reaction, so the oxygen evolution reaction activity is reduced and the adsorbate evolution mechanism (AEM) may become dominant. On the other hand, if the energy difference is excessively small compared to the aforementioned desirable range (e.g., less than 1.0 eV), the characteristics of the Ru-O bond may be excessively altered, causing unexpected effects on lattice stability or resulting in a negligible additional OER activity enhancement effect.

[0073] In one embodiment of the present invention, X-ray diffraction (XRD) is used to analyze the crystal structure and average grain size of the catalyst. The identification of a specific crystal structure (e.g., rutile RuO₂) serves as a criterion for determining the phase purity of the catalyst, and the grain size may be related to the specific surface area of ​​the catalyst, the degree of exposure of active sites, and sometimes stability. In one embodiment of the present invention, the synthesized nanostructured catalyst has nanometer-sized grains similar to the primary particle size, and this characteristic may affect the reactivity and overall performance of the catalyst.

[0074] In one embodiment of the present invention, the catalyst may have an average grain size of 7 nm or more, 8 nm or more, or 9 nm or more as a lower limit based on XRD analysis results, and may have an upper limit of 15 nm or less, 14 nm or less, or 13 nm or less. If the grain size is excessively small below the above-described preferred range, crystallinity may be reduced or structural instability may increase due to very small particles, thereby reducing the long-term durability of the catalyst. On the other hand, if the grain size is excessively large beyond the above-described preferred range, the number of active sites per unit mass decreases and the specific surface area decreases, which may lower the overall reaction activity of the catalyst.

[0075] In one embodiment of the present invention, Ru K-edge XANES is a powerful analytical tool that provides information on the average oxidation state and local electronic structure of ruthenium (Ru) atoms. In the XANES spectrum, the position of the edge energy is directly correlated with the oxidation state of the metal center, and generally, as the edge energy shifts to a higher value, it means that the average oxidation state of the metal is higher. In one embodiment of the present invention, the oxidation state of Ru is controlled by introducing d0 metal ions, and this changed oxidation state of Ru can be utilized to investigate the effect on oxygen evolution reaction (OER) activity.

[0076] In one embodiment of the present invention, the catalyst may have a tip energy measured in a Ru K-edge XANES spectrum that is 22125.90 eV or higher, or 22125.95 eV or higher, or 22126.00 eV or higher, or 22126.05 eV or higher as a lower limit, and 22126.30 eV or lower, or 22126.25 eV or lower, or 22126.20 eV or lower, or 22126.15 eV or lower as an upper limit. If the tip energy is lower than the above-described preferred range, the average oxidation state of Ru is not sufficiently high, so it fails to form an optimal electronic structure for OER activity, which may lead to a decrease in catalytic activity. On the other hand, if the tip energy is excessively high and the oxidation state of Ru increases excessively, it may contribute to an improvement in activity within a certain range, but excessive oxidation may instead cause instability of Ru species or promote unwanted side reactions.

[0077] In one embodiment of the present invention, Fourier-transformed extended X-ray absorption microstructure (FT-EXAFS) analysis provides quantitative information regarding local atomic arrangements and bond lengths around specific atoms. In the case of Ru K-edge EXAFS, the average bond length (Ru-O) and coordination number between Ru atoms and surrounding oxygen (O) atoms are analyzed to determine the effect of chemical modifications, such as the introduction of d0 metal ions, on the local structure and bonding characteristics of Ru centers. In one embodiment of the present invention, changes in Ru-O bond length are correlated with changes in Ru-O covalent bonding, and can be examined as factors affecting the OER activity mechanism and performance of the catalyst.

[0078] In one embodiment of the present invention, the average bond length indicated by the main peak position corresponding to the Ru-O bond during FT-EXAFS analysis may be shorter than the Ru-O bond length of a RuO₂ catalyst prepared by the same method without introducing Y, for example, when Y is introduced, and the specific numerical range can be determined through DFT calculation and precise analysis of experimental results. (Since quantitative bond length values ​​for EXAFS are not directly specified in the paper, a relative comparison or an explanation linked to DFT is required. If a numerical range must be included, a range of increase or decrease could be set based on the typical Ru-O bond length of RuO₂ (e.g., approximately 1.90 Å to 2.00 Å), but this is not specified in the paper.) If the Ru-O bond length is excessively long, OER activity may be reduced due to weakened Ru-O interactions and decreased covalent bonding. Conversely, if the Ru-O bond length becomes excessively short compared to the optimal range, it cannot be ruled out that it may cause unexpected stability problems or act adversely in specific reaction steps due to increased stress within the lattice or abrupt changes in the electronic structure.

[0079] In one embodiment of the present invention, mass activity is the current exhibited by the catalyst per unit mass and is an important indicator for evaluating the intrinsic efficiency and economic feasibility of the catalyst. High mass activity implies that a desired level of reaction rate (current density) can be achieved while using a small amount of precious metal catalyst, thus contributing to reducing catalyst costs and increasing practicality, particularly in PEMWE systems using expensive precious metals. In one embodiment of the present invention, it can be confirmed that a RuO₂ catalyst with introduced d0 metal ions exhibits significantly improved mass activity compared to conventional RuO₂ or commercial c-RuO₂.

[0080] A catalyst according to one embodiment of the present invention has a mass activity of 80 A g as its lower limit, measured at a potential of 1.45 V (vs. RHE) in a 0.5 M H₂SO₄ electrolyte. -1 More than, or 100 A g -1 More than, or 150 A g -1 More than, or 200 A g -1 More than, or 300 A g -1 It may be greater than, with an upper limit of 500 A g -1 Less than or equal to 450 A g -1 Less than or equal to 400 A g -1 Less than or equal to 380 A g -1 It may be lower than. If the mass activity is low below the aforementioned desirable range, the efficiency of the catalyst per unit mass decreases, requiring a larger amount of catalyst to obtain the desired current density, which may reduce economic feasibility. On the other hand, while it is generally positive for mass activity to be very high exceeding a specific range, it must be considered whether such high activity is balanced with long-term stability or other performance indicators, and there may exist a realistic upper limit achievable by a specific manufacturing method.

[0081] In one embodiment of the present invention, the electrochemical active surface area (ECSA) is an indicator representing the effective surface area of ​​a catalyst that can actually participate in an electrochemical reaction at the electrode-electrolyte interface, and is generally calculated through the measurement of double-layer capacitance (Cdl). ECSA is related to the roughness, porous structure, and number of exposed active sites of the catalyst, and for the same type of catalyst, a larger ECSA provides more active sites, which can contribute to increasing the overall reaction current. In one embodiment of the present invention, it can be observed that M-RuO₂ catalysts with d0 metal ions introduced and pure RuO₂ catalysts show a distinct difference in OER activity despite having similar ECSA values, which confirms that the improvement of the catalyst's intrinsic activity, rather than an increase in ECSA, is the main effect of introducing d0 metal ions.

[0082] A catalyst according to one embodiment of the present invention has an ECSA calculated from electrochemical double-layer capacitance measurements as a lower limit of 120 cm 2 More than, or 130 cm 2 More than, or 140 cm 2 It may be more than, with an upper limit of 200 cm 2 Less than, or 190 cm 2 Less than, or 180 cm 2 Less than, or 175 cm 2It may be lower than. If the ECSA is lower than the aforementioned desirable range (e.g., commercial c-RuO₂), the number of electrochemically accessible active sites is absolutely insufficient, which may limit the overall performance of the catalyst. On the other hand, if the ECSA is excessively large beyond the aforementioned range, this may imply a very fine particle size or a complex internal pore structure; however, such a structure does not always guarantee improved mass transfer characteristics or stability, and in the present invention, the enhancement of intrinsic activity under similar ECSA conditions is of greater significance than the size of the ECSA itself.

[0083] In one embodiment of the present invention, one of the important indicators for evaluating the durability of a catalyst is measuring the amount of active metal leached into the electrolyte during electrochemical operation. In particular, for ruthenium (Ru)-based oxygen evolution (OER) catalysts, it is known that the main degradation mechanism is the oxidation of Ru and its leaching in a soluble form such as RuO₄ during long-term operation in an acidic environment, which leads to a continuous decrease in catalyst activity and a shortened lifespan of the water electrolysis system. Therefore, by quantitatively analyzing the amount of Ru leached under specific conditions using inductively coupled plasma mass spectrometry (ICP-MS), the chemical stability and long-term durability of the catalyst can be directly evaluated, and the effect of strategies such as the introduction of d0 metal ions on Ru stabilization can be determined.

[0084] A catalyst according to one embodiment of the present invention is 10 mA cm⁻¹ in a 0.5 M H₂SO₄ electrolyte. -2When operated for 10 hours at a current density, the amount of Ru leached into the electrolyte may be, for example, 5.0 μg or less, 4.0 μg or less, 3.0 μg or less, 2.5 μg or less, or 2.0 μg or less. If the amount of Ru leached exceeds the aforementioned preferred range, this implies that the chemical stability of the catalyst is low, leading to rapid loss of the active material in an OER operating environment. Consequently, this results in a reduction in the active surface area of ​​the catalyst, a decrease in reaction activity, and rapid performance degradation, which may impose serious limitations on long-term actual application.

[0085] In one embodiment of the present invention, a key indicator for evaluating the activity of an oxygen evolution reaction (OER) catalyst is the overpotential required to achieve a specific current density. Overpotential is the voltage that must be applied in addition to the thermodynamic equilibrium potential; a lower value implies that the OER can be driven with less energy loss at the corresponding current density, which directly affects the overall energy efficiency and economic feasibility of the water electrolysis system. Therefore, a low overpotential reflects the superior intrinsic activity of the catalyst, which may be related to the optimization of the adsorption energy of reaction intermediates on the catalyst surface or the activation of more efficient reaction pathways (e.g., lattice oxygen-mediated mechanisms).

[0086] A catalyst according to one embodiment of the present invention is 10 mA cm⁻¹ in a 0.5 M H₂SO₄ electrolyte. -2The overpotential required to achieve the desired current density may be, for example, 300 mV or less, or 280 mV or less, or 260 mV or less, or 250 mV or less, or 230 mV or less. If the overpotential is high beyond the aforementioned desirable range, it indicates that the OER activity of the catalyst is relatively low, and more energy is consumed to generate the same amount of oxygen. Such high overpotentials ultimately lead to increased operating costs for the water electrolysis device and may suggest that the design of the catalyst's active sites or the reaction mechanism has not been optimized.

[0087] In one embodiment of the present invention, the Tafel slope is an important parameter for understanding the kinetic characteristics of the oxygen evolution reaction (OER). The Tafel slope represents the rate of change of the logarithmic value of current density with respect to changes in overpotential, and a smaller value implies that the current density can be effectively increased with a small increase in overpotential, suggesting faster reaction kinetics. Furthermore, the value of the Tafel slope can provide clues regarding the rate-determining step (RDS) and the main reaction mechanism of the OER, and is utilized to understand and improve the fundamental activity characteristics of the catalyst.

[0088] A catalyst according to one embodiment of the present invention has a Tafel slope measured in a 0.5 M H₂SO₄ electrolyte, for example, 60 mV dec -1 Less than, or 50 mV dec -1 Less than or equal to 45 mV dec -1 Less than, or 40 mV dec -1 Less than or equal to 35 mV dec -1It may be less than that. If the Tafel slope is large beyond the aforementioned desirable range, it means that the OER reaction kinetics are slow and the rate of increase in current density with increasing overpotential is low. This is a factor that significantly reduces operating efficiency, especially at high current densities, and may indicate that the reaction pathway on the catalyst surface is inefficient or that the energy barrier of the rate-determining step is high.

[0090] The second aspect of the present invention is,

[0091] The present invention provides a method for manufacturing a catalyst for an oxygen evolution reaction, comprising the steps of: preparing a zeolitic imidazolate framework (ZIF) template; contacting the ZIF template with an aqueous solution containing ruthenium ions and metal ions having a d0 electron configuration so that the ZIF template is gradually etched and simultaneously ruthenium and d0 metal precursors are formed; and heat-treating the ZIF template formed with the ruthenium and d0 metal precursors in air to obtain a ruthenium oxide catalyst having a porous structure as described in claim 1, into which the d0 metal ions are introduced.

[0093] Detailed explanations have been omitted for parts that overlap with the first aspect of the present invention, but the content described in the first aspect of the present invention may be applied equally even if such explanations are omitted in the second aspect.

[0095] Hereinafter, a method for manufacturing a catalyst for an oxygen generation reaction according to the second aspect of the present invention will be described in detail.

[0097] First, in one embodiment of the present invention, the method may include the step of preparing a zeolitic imidazolate framework (ZIF) template. Such a ZIF template can serve as a sacrificial framework to realize a nanometer-sized uniform porous structure and a high specific surface area of ​​the catalyst finally produced.

[0098] In one embodiment of the present invention, various types of zeolite imidazolate frameworks may be considered as the ZIF template, for example, ZIF-based materials composed of specific transition metal ions (e.g., zinc ions) and organic ligands of the imidazole or derivative series may be used. Such ZIF templates typically have relatively uniform particle sizes ranging from several nanometers to tens of nanometers and can be preferably used as sacrificial templates due to their well-developed microporous structure and the ability to be easily removed in subsequent processes. Selecting such an appropriate ZIF template has significant technical implications for producing a catalyst with a large reaction surface area and enhanced mass transfer characteristics by effectively controlling the hierarchical porous structure of the finally obtained catalyst, namely the size of primary and secondary particles, and the size and distribution of pores. Preferably, in one embodiment of the present invention, the ZIF template may be ZIF-8.

[0099] In one embodiment of the present invention, the preparation of the ZIF mold may include, according to one embodiment, a step of dissolving or dispersing a metal precursor (e.g., in the form of a metal salt) providing metal ions and an organic ligand in a suitable solvent (e.g., an alcoholic solvent) under an appropriate stoichiometric ratio or specific reaction conditions (e.g., a ligand excess condition), then mixing them and reacting them while stirring at a specific temperature (e.g., room temperature or a controlled elevated temperature condition) for a certain period of time (e.g., in the range of minutes to tens of hours) to form ZIF particles. The ZIF particles thus formed may be obtained in powder form through a conventional solid-liquid separation method such as filtration or centrifugation, a solvent washing process for removing residual reactants, and a drying process at an appropriate temperature (e.g., in the range of about 50 °C to about 150 °C). Synthesis process variables of such ZIF templates, such as the type and concentration of precursors used, the selection of solvent, reaction temperature and time, and post-treatment conditions, can affect the particle size, crystallinity, morphology, pore characteristics, and yield of the manufactured ZIF templates, which can consequently indirectly contribute to the structural characteristics and overall performance of the final catalyst.

[0100] Next, in one embodiment of the present invention, the method may include the step of contacting the ZIF template with an aqueous solution containing ruthenium ions and metal ions having a d0 electron configuration so that the ZIF template is progressively etched while simultaneously forming ruthenium and d0 metal precursors. By uniformly depositing or forming ruthenium and d0 metal precursors simultaneously with the progressive etching of the ZIF template, a basis can be provided for effectively dispersing and introducing d0 metal ions into a ruthenium oxide matrix after final heat treatment.

[0101] In one embodiment of the present invention, a water-soluble ruthenium salt, such as ruthenium chloride (RuCl₃·xH₂O), may be used as the ruthenium ion source. Additionally, as a metal ion source having a d0 electron configuration, a nitrate or chloride of the corresponding metal may be used, and for example, yttrium nitrate hydrate (Y(NO₃)₂·6H₂O) for yttrium (Y) ions, cerium nitrate hydrate (Ce(NO₃)₂·6H₂O) for cerium (Ce) ions, lanthanum nitrate hydrate (La(NO₃)₂·6H₂O) for lanthanum (La) ions, or gadolinium nitrate hydrate (Gd(NO₃)₂·6H₂O) for gadolinium (Gd) ions may be used without limitation. The selection of these precursor materials determines the type and concentration of d0 metal ions in the ruthenium oxide ultimately formed, which can be an important factor in directly affecting the electronic structure and OER activity of the catalyst.

[0102] In one embodiment of the present invention, the concentration and ratio of ruthenium ions and d0 metal ions in the aqueous solution may be adjusted to optimize the composition and performance of the final catalyst. For example, in one embodiment of the present invention, the total amount of metal precursor per 100 mg of ZIF template may be added in a specific range (e.g., an amount corresponding to about 150 mg of RuCl₃·xH₂O and about 61 mg of Y(NO₃)₂·6H₂O), and this ratio may be adjusted according to the target doping concentration of d0 metal ions (e.g., about 1 at% to 10 at%). The reaction between the aqueous solution and the ZIF template may typically proceed under stirring at room temperature for a certain period of time (e.g., tens of minutes to several hours), and during this process, ruthenium and d0 metal hydroxides or similar precursors may be precipitated or deposited on the etched surface or exposed internal space along with gradual etching through hydrolysis of the ZIF template. This simultaneous etching and precipitation process induces metal precursors to be mixed very uniformly at the nanoscale, which can contribute to the formation of a homogeneous solid solution or a highly dispersed composite oxide during subsequent heat treatment.

[0103] Next, in one embodiment of the present invention, the method may include the step of heat-treating a ZIF template formed with the ruthenium and d0 metal precursors in air to obtain a ruthenium oxide catalyst having a porous structure into which the d0 metal ions are introduced. This heat-treating step in air can serve to remove residues from the ZIF template and crystallize the metal precursor into a ruthenium oxide with a stable rutile structure, while simultaneously incorporating the d0 metal ions into the ruthenium oxide lattice or strongly binding them to the surface to form a final active catalyst phase.

[0104] In one embodiment of the present invention, the heat treatment process may be performed within a specific temperature range, for example, in a range of about 300°C to about 400°C, more specifically at a temperature near about 350°C for a certain period of time (e.g., 1 hour to 5 hours, preferably about 2 hours). The heating rate during heat treatment is also a variable that can be controlled, for example, by heating at a relatively slow rate of about 1°C to 10°C per minute, preferably about 2°C per minute, to prevent rapid decomposition or crystal growth of the precursor and to induce the formation of a uniform oxide. These conditions, such as the heat treatment temperature and time, and the heating rate, affect the crystallinity, particle size, defect structure, and distribution of d0 metal ions of the finally obtained ruthenium oxide, and this may have significant technical implications for the electrochemical activity and stability of the catalyst. For example, excessively low heat treatment temperatures can cause incomplete oxidation or low crystallinity of the precursor, while conversely, excessively high temperatures can lead to particle growth, reduced specific surface area, or unwanted phase changes; therefore, selecting appropriate heat treatment conditions is important for optimal catalyst performance.

[0105] Regarding the heat treatment atmosphere, one embodiment of the present invention may include performing heat treatment in air. Heat treatment in an air atmosphere generally provides an oxidizing atmosphere effective for converting metal precursors into corresponding metal oxides. This can facilitate the conversion of ruthenium and d0 metal precursors into ruthenium oxide and oxides of the corresponding d0 metal, respectively, or the substitution or interstitial incorporation of d0 metal ions into the ruthenium oxide lattice. Additionally, when using organic-based molds such as ZIF molds, heat treatment in air can help in the complete combustion and removal of organic components, thereby contributing to obtaining a porous structure based on pure metal oxides. In other embodiments, depending on the specific purpose, partial utilization of an inert gas atmosphere or a reducing gas atmosphere, or controlling the atmosphere by dividing the heat treatment steps into multiple stages, may be considered; however, oxidative heat treatment in air can be effectively used to realize the catalytic properties of the present invention.

[0107] The third aspect of the present invention is,

[0108] The present invention provides a proton exchange membrane water electrolysis device comprising an anode; a cathode; and a proton exchange membrane disposed between the anode and the cathode, wherein the anode comprises the catalyst.

[0110] Detailed explanations have been omitted for parts that overlap with the first and second aspects of the present invention; however, the contents described for the first and second aspects of the present invention may be applied equally to the third aspect even if such explanations are omitted.

[0112] Hereinafter, a proton exchange membrane water electrolysis device according to the third aspect of the present invention will be described in detail.

[0114] In one embodiment of the present invention, the anode in the proton exchange membrane water electrolysis device is an electrode where an oxygen evolution reaction (OER) occurs to generate oxygen gas through the electrolysis of water, and a ruthenium oxide-based catalyst with d0 metal ions introduced according to one embodiment of the present invention can be effectively applied. In this case, the catalyst can typically be supported on a conductive support or a gas diffusion layer (GDL) to form a membrane-electrode assembly (MEA).

[0115] In one embodiment of the present invention, the cathode is an electrode in which a hydrogen evolution reaction (HER) occurs, in which hydrogen ions are reduced to generate hydrogen gas, and can typically be used in a form in which a precious metal catalyst, such as platinum (Pt) or a platinum-based alloy, is supported on a carbon support (e.g., Pt / C). The cathode catalyst layer can also be in contact with a gas diffusion layer to facilitate the supply of electrons and the discharge of the generated hydrogen gas.

[0116] In one embodiment of the present invention, the proton exchange membrane is a proton (H) generated at the anode + It is a solid polymer electrolyte membrane that selectively moves ) to the cathode while simultaneously serving as a physical separation and electronic insulation between the anode and the cathode. As such a proton exchange membrane, perfluorosulfonic acid (PFSA) series ionomer membranes (e.g., Nafion®) can be widely used due to their excellent proton conductivity and chemical and mechanical stability.

[0117] In addition, in one embodiment of the present invention, the proton exchange membrane water electrolysis device may further include a gas diffusion layer, bipolar plates, or, in the case of a single cell, monopolar plates for supplying reactants, discharging products, electrical connection, and mechanical support. The gas diffusion layer may be made mainly of a porous carbon material (e.g., carbon paper, carbon cloth) or a corrosion-resistant porous metal body (e.g., titanium felt) to perform the role of a diffusion layer for reaction gases and a current collector, and the bipolar plates may provide a passage to uniformly distribute reactants (water) to each electrode surface through internal flow channels and to discharge the generated gas to the outside.

[0118] In one embodiment of the present invention, the catalyst loading amount at the anode is 2.0 mgcat cm⁻¹ -2 Up to 4.0 mg cat cm -2 This can be a range. This catalyst loading range can contribute to ensuring economic viability by providing sufficient active sites for an effective oxygen evolution reaction while managing the usage of the precious metal ruthenium at a reasonable level.

[0119] In one embodiment of the present invention, the proton exchange membrane water electrolysis device may be operated at an operating temperature of 80 °C to 100 °C. Operation at such a relatively high temperature is advantageous for improving electrode reaction kinetics and increasing the ion conductivity of the proton exchange membrane, thereby increasing the energy efficiency of the entire water electrolysis system, and the catalyst of the present invention can exhibit stable performance even in such a high-temperature environment.

[0120] In one embodiment of the present invention, the proton exchange membrane water electrolysis device has a cell voltage of 1.6 V and a pressure of 1.0 A cm -2It may indicate a current density as described above. Achieving a high current density at a relatively low cell voltage implies that the water electrolysis device to which the catalyst of the present invention is applied possesses excellent energy conversion efficiency and a high hydrogen production rate, which can serve as an indicator of improved performance compared to commercial catalyst systems.

[0121] In one embodiment of the present invention, the proton exchange membrane water electrolysis device has a pressure of 200 mA cm⁻¹ -2 When operating for 100 hours at a current density, the cell voltage rise can be 20 mV or less. The small rise in cell voltage during long-term continuous operation suggests that the catalyst of the present invention maintains high chemical and structural stability even under harsh oxygen evolution reaction conditions in an acidic environment, thereby minimizing performance degradation, which demonstrates that practical durability can be secured for catalysts based on lattice oxygen-mediated mechanisms.

[0123] Hereinafter, embodiments of the present invention are described in detail so that those skilled in the art can easily implement the invention. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein.

[0125] Example 1: Synthesis of ZIF-8 Template

[0126] To synthesize the ZIF-8 template, 4.1 g of Zn(NO₃)₂·6H₂O was dissolved in 250 mL of methanol, and separately, 7.445 g of 2-methylimidazole (2-min) was dissolved in 250 mL of methanol and vigorously stirred for 30 minutes. Afterward, the Zn(NO₃)₂·6H₂O methanol solution was poured into the 2-min methanol solution and stirred for 5 hours to obtain a ZIF-8 colloidal solution. This colloidal solution was centrifuged and washed three times with methanol. Finally, ZIF-8 powder was obtained by drying at 80 °C for 10 hours.

[0128] Example 2: Synthesis of M-RuO₂ Electrocatalyst

[0129] For the synthesis of the M-RuO₂ electrocatalyst, 100 mg of dried ZIF-8 powder was dispersed in 30 mL of H₂O, and then 10 mL of a metal aqueous solution was added. The metal aqueous solution was prepared by dissolving RuCl₃·xH₂O and the metal salts to be introduced (Y(NO₃)₂·6H₂O, Ce(NO₃)₂·6H₂O, La(NO₃)₂·6H₂O, Gd(NO₃)₂·6H₂O) in deionized water (DI water). Generally, 150 mg of RuCl₃·xH₂O and 61 mg of Y(NO₃)₂·6H₂O were used for the synthesis of Y-RuO₂; for Ce-RuO₂, La-RuO₂, and Gd-RuO₂, 69 mg of Ce(NO₃)₂·6H₂O, 69 mg of La(NO₃)₂·6H₂O, and 72 mg of Gd(NO₃)₂·6H₂O, respectively, were used instead of 61 mg of Y(NO₃)₂·6H₂O. For pure RuO₂, only 200 mg of RuCl₃·xH₂O was used. After the reaction, the solution was centrifuged and washed three times with DI water. Finally, the solution was dried at 80 °C for 10 hours and then calcined in an air atmosphere at 350 °C for 2 hours (heating rate: 2 °C min -1 An M-RuO₂ electrocatalyst was obtained by )

[0131] Material property analysis

[0132] The morphology of the electrocatalysts was investigated using a transmission electron microscope (TEM, FEI Tecnai G2 F30 S-Twin) and a high-resolution dual-spherical aberration-corrected TEM (Thermo Fisher Scientific Spectra Ultra). The crystal structure of the electrocatalysts was characterized by X-ray diffraction (XRD, Rigaku SmartLab, Cu Kα radiation) analysis. The surface area was measured by N₂ physisorption analysis (Micromeritics Tristar II 3020) at 77 K. X-ray photoelectron spectroscopy (XPS) was performed using a Thermo Fisher Scientific K-Alpha+ XPS. The detailed electronic and local atomic structures of the electrocatalysts were analyzed by X-ray absorption spectroscopy (XAS) at the 10C Wide XAFS beamline of the Pohang Accelerator Laboratory (PAL, South Korea).

[0134] Electrochemical measurement

[0135] To prepare the working electrode, 5 mg of the prepared electrocatalyst and 1 mg of acetylene black were dispersed in 1 mL of a mixed solution of DI water, isopropanol, and 5 wt% Nafion® solution (DI water : isopropanol : 5 wt% Nafion® solution = volume ratio 0.485 : 0.485 : 0.03). Subsequently, 10 μL of this solution was dropped onto a glassy carbon electrode (GCE, diameter 5 mm) and dried at room temperature. The electrocatalyst loading on the GCE was 0.255 mg cm⁻¹. -2 It corresponded to. Ag / AgCl (saturated KCl solution) was used as the reference electrode, and a platinum wire was used as the counter electrode. Cyclic voltammetry (CV) was performed in an O₂-saturated 0.5 M H₂SO₄ aqueous solution at 1600 rpm and 10 mV s⁻¹. -1 It was performed at a scan rate of . The chronopotentiometry test was 10 mA cm⁻¹. -2It was performed at a current density. CV curves for electrochemical surface area (ECSA) measurements were obtained at various scan rates in a potential range of 0.93–1.03 V (vs. RHE).

[0137] Real-time differential electrochemical mass spectrometry (Operando DEMS) measurement

[0138] For real-time DEMS measurements, a custom-made electrochemical cell connected to a mass spectrometer (Max 300 LG, Extrel) was used. The DEMS signal is 1 1 mV s⁻¹ within a potential range of 1.25–1.50 V (vs. RHE) in a 0.5 M H₂SO₄ solution labeled with the 8O isotope -1 It was collected during three consecutive linear scan voltammetry (LSV) scans at a rate of . Before each LSV scan, the potential was maintained at 1.25 V (vs. RHE) to stabilize the mass signal. The cell's ohmic drop was corrected (85%) using a manual iR compensation (MIR) program. At mass-to-charge ratios (m / z) = 36, 34, and 32, respectively 36 O₂, 34 O₂, 32 The mass signal for O₂ was monitored. However, the Ar contribution at m / z = 36 was corrected by subtracting 0.337% of the m / z = 40 signal.

[0140] Single cell measurement

[0141] A membrane-electrode assembly (MEA) for a single cell of a proton exchange membrane water electrolysis (PEMWE) was fabricated by inserting a Nafion 212 membrane (50.8 μm) between the anode and cathode without hot pressing (the geometric active area of ​​the MEA is 2.2 × 2.3 cm²). 2(It was fixed as ). The cathode was 0.4 mgPt cm⁻¹ on carbon paper (Sigracet 39BB, 315 μm) using commercial Pt / C ink (composed of Pt / C (46.9 wt%, TEC10E50E, TKK), 5 wt% Nafion® solution, isopropanol, and DI water in a weight ratio of 5:32:126:160). -2 The anode was fabricated by spraying with a catalyst loading amount of 3.0 mgcat cm⁻¹. The anode was prepared by spraying the fabricated Y-RuO₂ and commercial RuO₂ ink (composed of electrocatalyst, 5 wt% Nafion® solution, isopropanol, ethanol, and DI water in a weight ratio of 5:11:118:59:75) onto a Pt-coated titanium fiber felt (260 μm) at a amount of 3.0 mgcat cm⁻¹. -2 It was fabricated by spraying with a catalyst loading amount. Single-cell tests were performed using the potentiostatic method at 90 °C in an electrolytic cell test station (CNL Energy); after stabilizing for 1 minute at each voltage, measurements were taken at 0.05 V intervals from 1.30 V cell to 2.00 V cell. 15 mL min of preheated deionized water was added to the anode side. -1 Injection was performed at a rate of [value]. Electrochemical impedance spectroscopy (EIS) analysis was performed at 1.6 V cells with an amplitude of 10 mV and a frequency range of 50 kHz to 1 Hz. The obtained high-frequency resistance (HFR) was used to calculate the resistance overpotential (ηohm) and to construct an HFR-free Tafel plot. To refine the overpotential in PEMWE, the activation overpotential (ηact) was derived from the HFR-free Tafel equation, and the remaining voltage loss was assumed to be the mass transfer overpotential (ηmt).

[0143] Density Function of the Fourier Transform (DFT) calculation

[0144] Spin polarization DFT calculations were performed using the Vienna Ab initio simulation package. Exchange correlation energy effects were implemented using the Generalized Gradient Approximation (GGA) with Perdew-Burke-Ernzerhof (PBE) functionals. A plane wave basis with a cutoff energy of 400 eV was used, and the projector constructive wave method was used to account for interactions between the atomic nucleus region and electrons. All structural optimizations were performed until atomic forces were minimized to less than 0.05 eV / Å. An empirical DFT-D3 method with zero damping was used to account for dispersion interactions between the adsorbate and the surface metal oxide. An orthogonal (1×3) cell of rutile RuO₂ (110) composed of three layers was used. Surface doping was modeled by substituting two surface Ru atoms as shown in Fig. 22. To avoid spurious interactions between surface slabs, a vacuum space of 20 Å in the z-direction was applied, and the bottommost atomic layer was fixed in the bulk position. The total energy was calculated using 3×2×1 k-point mesh sampling in the Brillouin domain. All structural visualizations were performed using VESTA software. Atomic charge analysis was performed using the Bader charge splitting method. The Gibbs free energy was obtained by applying the thermal correction derived from frequency calculations to the total DFT energy. The OER overpotential from the Gibbs free energy was calculated following previous studies. The potential determination step (PDS) is the step requiring the largest electrochemical driving force, which is 4e of the OER. - It corresponds to the change in Gibbs free energy of each proton-bonded electron transport step along the pathway. By calculating the change in Gibbs free energy Gn (n=1,2,3,4) of each proton-bonded electron transport step, the Gibbs free energy of PDS was obtained as follows:

[0145]

[0146] Then the OER overvoltage was as follows:

[0147]

[0148] Here, 1.23V is 4e - It was the equilibrium potential of the OER reaction.

[0150] Experimental Example: Each experimental result

[0151] In this study, RuO₂ electrocatalysts with introduced d0 metal ions were synthesized using the sacrificial template method. A zeolite imidazolate framework (ZIF) was used as the template. The ZIF template was synthesized by mixing a methanol solution of zinc nitrate and 2-methylimidazole, resulting in tetrahedral coordination Zn ions composed of particles approximately 20 nm in size connected by 2-methylimidazole. 2+ ZIF-8 particles containing ions were obtained (Fig. 2). Subsequently, the ZIF template was Ru 3+ A RuO₂ electrocatalyst with introduced dO metal ions was obtained by progressively etching through hydrolysis by dO metal ions and undergoing an additional heat treatment process (Fig. 3). The synthesized electrocatalyst was named M-RuO₂ depending on the type of introduced dO metal ions (M = Y, Ce, Gd, La).

[0152] In high-angle annular dark-field scanning transmission electron microscope (HAADF-STEM) images (Figs. 3b to 3d, Figs. 4 to 7), the M-RuO₂ electrocatalyst clearly showed well-defined lattice stripes corresponding to the (110) plane of RuO₂, exhibiting a structure in which nanometer-scale primary particles aggregate to form secondary particles on the scale of hundreds of nanometers, and interparticle pores are present between the primary particles. Additionally, energy-dispersive X-ray spectroscopy (EDS) elemental mapping confirmed that d0 metal ions were uniformly introduced into the RuO₂ matrix. The doping content and Ru mass fraction of each catalyst, confirmed by STEM-EDS, are presented in Table 1.

[0153] electrocatalyst (Electrocatalysts) Ru (wt %) Second metal (effective metal) Secondary metal (wt %) RuO2 71.81 - Y-RuO2 70.92 3.04 Ce-RuO2 72.71 1.58 Gd-RuO2 72.74 2.76 La-RuO2 75.33 1.09

[0154] To investigate the surface area of ​​the M-RuO₂ electrocatalysts, nitrogen adsorption-desorption isotherm analysis was performed at 77 K (Fig. 8). All electrocatalysts had surface areas of 49.1–64.2 m² when calculated using the Brunauer-Emmett-Teller (BET) method. 2 g -1 They exhibited similar surface areas within the range. Furthermore, these catalysts showed significantly higher surface areas and pore volumes than commercial RuO₂ (c-RuO₂) due to intergranular pores formed mainly between primary particles (Table 2). The X-ray diffraction (XRD) pattern of M-RuO₂ was confirmed to have a rutile RuO₂ structure (JCPDS 71-2273; Fig. 9a). The average grain size of M-RuO₂ was calculated to be in the range of 8.2–13.5 nm, similar to the primary particle size of M-RuO₂ (Table 3).

[0155] electrocatalyst (Electrocatalysts) BET surface area BET surface area (m 2 g -1 ) Pore ​​volume Pore ​​volume (cm 3 g -1 ) RuO2 49.1 0.13 Y-RuO2 58.0 0.19 Ce-RuO2 55.1 0.16 Gd-RuO2 64.2 0.21 La-RuO2 53.0 0.17 c-RuO2 8.5 0.04

[0156] electrocatalyst (Electrocatalysts) Average grain size Average crystalline size (nm) RuO2 9.7 Y-RuO2 13.5 Ce-RuO2 13.3 Gd-RuO2 9.7 La-RuO2 8.2

[0157] The electronic structure of the M-RuO₂ electrocatalyst was evaluated using X-ray photoelectron spectroscopy (XPS) and X-ray absorption spectroscopy (XAS). The high-resolution O 1s XPS spectrum of the electrocatalyst shows lattice oxygen (O at approximately 529.5 eV). L ), oxygen vacancies of approximately 531 eV (O V ), and adsorbed H₂O (H₂O₂) of approximately 533 eV ad It was deconvolved into three components of ) (Fig. 9b, Fig. 10). Compared to the deconvolution results of the O 1s spectrum of RuO₂, M-RuO₂ containing Y, Gd, and La is O L Big O V While the ratio showed a decreasing trend, Ce-RuO₂ exhibited the opposite trend (Fig. 9c, Table 4). This indicates that introducing Y, Gd, and La to RuO₂ can form and stabilize an oxygen-vacancy-rich surface. In the high-resolution Ru 3d XPS spectrum, Ru 4+ 3D5 / 2 and 3d 3 / 2 Two sets of doublet peaks and corresponding satellite peaks originating from the arrangement were observed. In Y-RuO₂, the binding energy of Ru 3d shifted in the positive direction by 0.1 eV compared to RuO₂, indicating a slight increase in the oxidation state of Ru. Similarly, the binding energy of Ru 3d in Gd-RuO₂ and La-RuO₂ also shifted in the positive direction by 0.05 eV compared to RuO₂ (Fig. 9d). In contrast, Ce-RuO₂ shifted slightly in the negative direction compared to RuO₂, indicating a decrease in the oxidation state. These opposing trends could have been primarily due to the different oxidation states of the introduced metal ions. The XPS spectra of Y, Gd, and La are typical M 3+ While it exhibited ionic characteristics, the Ce 3d XPS spectrum showed Ce near 917 eV 4+ It exhibited a characteristic peak (Fig. 11). Previous reports have suggested that Ru species in higher oxidation states exhibit better OER activity. This enhancement may be attributed to strong dd-coulomb interactions resulting from the increased oxidation state of Ru. These interactions split the antibonding band into an empty upper Hubbard band (UHB) and a filled lower Hubbard band (LHB), causing a downward shift of the metal d-band and a relative upward shift of the O 2p-band.

[0158] electrocatalyst (Electrocatalysts) O L O v H 2 O ad O V / O L RuO2 31.26 56.31 12.42 1.80 Y-RuO2 26.61 61.55 11.84 2.31 Ce-RuO2 32.82 54.51 12.67 1.66 Gd-RuO2 29.82 58.68 11.5 1.97 La-RuO2 29.5 58.35 12.15 1.98

[0159] To investigate the electronic structure of Ru in greater depth, X-ray absorption near-linear spectral analysis (XANES) was performed on M-RuO₂, c-RuO₂, and Ru foils (Fig. 9e). The shoulder observed near the absorption threshold of the Ru foil is the result of the dipole-forbidden transition from Ru 1s to 4d due to Ru 4d-5p mixing. In the case of M-RuO₂ and c-RuO₂, this shoulder is weakened as mixing between 4d and 5p orbitals within the RuO₂ lattice is prevented. Additionally, the absorption edge shifts to a higher energy level compared to the Ru foil, reflecting the increased oxidation state of Ru. In XANES, the oxidation state of each material was determined by deriving the result of a linear fitting of the edge energy (determined by the maximum value of the first derivative) relative to the reference material. Y-, Gd-, and La-RuO₂ exhibited higher Ru oxidation states than RuO₂, whereas Ce-RuO₂ showed a lower oxidation state, which is in good agreement with the XPS results (Fig. 12). The local atomic environment of Ru is k in the R space. 2 - It was investigated using the weighted Fourier transform extended X-ray absorption fine structure (FT-EXAFS) (Fig. 9f). The FT-EXAFS spectrum revealed that the Ru-O bond length in Y-RuO₂ is shorter than that in RuO₂, which may indicate stronger covalent bonding of Ru-O bonds in Y-RuO₂. Additionally, it was confirmed that Ce-RuO₂ has longer Ru-O bonds compared to RuO₂. Therefore, the observed trends regarding Ru oxidation state and Ru-O bond covalent bonding in the M-RuO₂ electrocatalyst were consistent with the trends observed regarding Ru-O bond length.

[0160] To investigate the effect of introduced d0 metal ions on OER activity, the OER activity of the M-RuO₂ electrocatalyst was first evaluated using a standard three-electrode system with a rotating disk electrode in a 0.5 M H₂SO₄ electrolyte. Capacitive current was compensated by averaging the forward and reverse scans obtained from cyclic voltammetry (CV) measurements. Resistance loss was corrected by subtracting the iR voltage drop using the electrolyte resistance determined by electrochemical impedance spectroscopy (EIS) analysis at the open-circuit potential. 10 mA cm⁻¹ -2 The overpotential required to reach [value] was 357 mV for c-RuO₂ and 270 mV for the RuO₂ electrocatalyst synthesized in this study. The introduction of d0 metal ions exhibited various effects on OER; the introduction of Y, Gd, and La enhanced OER activity, whereas the introduction of Ce resulted in a decrease in OER activity. Specifically, Y-RuO₂ demonstrated excellent OER activity, reaching 10 mA cm⁻¹ at an overpotential of 227 mV. -2 A current density was achieved (Figs. 13a, 13b). Furthermore, Y-RuO₂ exhibited OER mass activity 77.3 times and 7.7 times higher than c-RuO₂ and RuO₂, respectively, at 1.45 V (Fig. 14).

[0161] To further compare the OER activity of the electrocatalysts, the electrochemical active surface area (ECSA) was calculated based on the double-layer capacitance (Cdl) through cyclic voltammetry (CV) measurements at various scan rates (Figs. 15 and 16a; Table 5). The calculated ECSAs were similar for all electrocatalysts due to their identical structures. Consequently, the OER inactive trend, expressed by normalizing the measured OER current by ECSA, matched the trend of the geometric current density (Fig. 16b). This result indicates that the enhanced OER activity is due to the improvement in intrinsic OER activity after introduction, rather than an increase in ECSA. To further analyze the OER kinetics of the M-RuO₂ electrocatalyst, the Tafel slope was calculated from the obtained LSV polarization curves. Y-RuO₂ is RuO₂ (45.8 mV dec -1 ) and c-RuO₂(74.4 mV dec -1 Improved Tafel slope (34.9 mV dec) compared to ) -1 By showing ), enhanced OER kinetics were demonstrated in Y-RuO₂ (Fig. 13c). Furthermore, significant differences in Tafel slopes may indicate that the rate-determining step may differ in these electrocatalysts.

[0162] electrocatalyst (Electrocatalysts) ECSA (cm 2 ) RuO2 144.4 Y-RuO2 173.5 Ce-RuO2 144.5 Gd-RuO2 170.3 La-RuO2 162.8 c-RuO2 29.3

[0163] Considering that the main concern regarding Ru-based OER electrocatalysts is durability, to verify this, 10 mA cm⁻¹ -2Changes in overpotential were measured for 40 hours. The durability of the RuO₂ electrocatalyst decreased rapidly and lasted for less than 12 hours. In contrast, Y-RuO₂ showed stable operation with a slight increase in overpotential over 40 hours, demonstrating better durability compared to RuO₂ under acidic OER conditions (Fig. 13d). The mass of Ru eluted during the stability test was further measured using inductively coupled plasma mass spectrometry (ICP-MS). While 8.81 μg of Ru eluted from RuO₂ over 10 hours, only 1.98 μg of Ru eluted from Y-RuO₂ during the same period, and 2.63 μg eluted after 40 hours, demonstrating superior stability (Table 6).

[0164] electrocatalyst (Electrocatalysts) Leached Ru mass Dissolve Ru mass (μg) RuO2(10 h) 8.81 Y-RuO2(10 h) 1.98 Y-RuO2(20 h) 2.38 Y-RuO2(40 h) 2.63

[0165] Ex-situ XANES and EXAFS analyses were performed on the Ru K-edge to investigate changes in electronic structure and local atomic environment after a 10-hour stability test. In the Ru K-edge XANES spectrum, RuO₂ showed a relatively larger shift in the absorption end position compared to Y-RuO₂, indicating significant oxidation of Ru in RuO₂ (Fig. 17a). Furthermore, the FT-EXAFS spectrum showed a decrease in peak intensity and bond length corresponding to the Ru-O bond in RuO₂, demonstrating degradation due to Ru peroxidation (Fig. 17b). In contrast, Y-RuO₂ showed almost no change in peak intensity and bond length in the FT-EXAFS spectrum after OER, further supporting its excellent stability. Due to the strong oxygen-philicity of Y, it will recover oxygen vacancies formed after LOM, contributing to improved stability.

[0166] To experimentally verify the change in the OER mechanism caused by the introduction of d0 metal ions, 18Real-time differential electrochemical mass spectrometry (DEMS) measurements were performed using the O isotope labeling method (Figs. 13e, 13f, Fig. 17). DEMS measurements were performed on the grid 16 RuO₂ electrocatalyst containing O and 1 Electrolyte containing 8O (H₂ 18 It was performed using an O-based 0.5 M H₂SO₄ electrolyte. As mentioned in the introduction, since oxygen species in the electrolyte react to produce oxygen gas in AEM, 36 O₂( 1 8O 1 8O) is generated. On the other hand, in LOM, since lattice oxygen participates in the reaction 32 O₂( 16 O 16 O) or 34 O₂( 16 O 1 8O) is generated. In c-RuO₂, originating from AEM 36 While only a significant mass signal for O₂ was detected, originating from LOM 32 No mass signal for O₂ was observed, and 34 The mass signal for O₂ was negligible (Fig. 18). In the RuO₂ of this study, compared to c-RuO₂ 34 The mass signal for O₂ was slightly increased, suggesting that some of the oxygen generated by the LOM may be attributed to its low crystallinity and defect-rich characteristics. However, 34 The mass signal for O₂ is still 36 It was much smaller than the signal for O₂ (Fig. 13e). Therefore, it can be inferred that the main OER mechanism for RuO₂ in this study is AEM. In contrast to RuO₂ and c-RuO₂, in Y-RuO₂ 34 The mass signal for O₂ increased significantly, and 32A distinct mass signal for O₂ was observed, indicating the activation of lattice oxygen and participation in OER through LOM (Fig. 13f). The lattice oxygen participation rate calculated based on the mass signal peak area was 49.4% for Y-RuO₂, whereas RuO₂ in this study was 19.3% and c-RuO₂ was 4.2%.

[0167] To further analyze the OER mechanism of the electrocatalyst, O₂ derived from LOM 2- Tetramethylammonium cations (TMA) that strongly interact with anionic oxygenation species such as + Electrochemical OER measurements were performed using 0.5 M H₂SO₄ and 0.01 M TMA + In the electrolyte, Y-RuO₂ is 10 mA cm⁻¹ -2 In Y-RuO₂, the overpotential increased significantly from 227 mV to 289 mV, whereas RuO₂ and c-RuO₂ showed a relatively small increase in overpotential, consistent with the DEMS analysis results (Fig. 19). Based on these results, the improved OER performance in Y-RuO₂ compared to RuO₂ and c-RuO₂ is attributed to a change in the OER mechanism. Synthesizing the results of the material analysis and electrochemical analysis, it is suggested that the inclusion of d0 metal ions alters the OER mechanism, thereby enhancing the electrocatalytic OER activity of RuO₂.

[0168] To further elucidate the fundamental causes of the enhanced OER kinetics and mechanism, the electronic structure and adsorption energies of reaction intermediates were investigated through Density Functional Theory (DFT) calculations. For the DFT calculations, an orthogonal (1×3) cell of rutile RuO₂ (110) composed of three layers was used. Surface doping was modeled by substituting two surface Ru atoms as shown in Fig. 20. Figs. 21a and 21b show the Gibbs free energy diagrams for all basic reaction steps of AEM and LOM related to acidic OER at each surface. In the conventional AEM, H₂O molecules generate O₂ through *OH, *O, and *OOH intermediates via four proton-electron linked transport steps at the surface metal-ion center. In contrast, in the LOM, O₂ is generated through the bonding of adsorbed O with lattice O without a *OOH formation step. The formed oxygen vacancies are subsequently filled with OH dissociated from H₂O. Therefore, the adsorption energies for the first two steps were calculated identically regardless of the mechanism, and the difference between the two mechanisms appeared in the third step. *OH, *O, *OOH, and *OH for the reaction pathway Vo-site The optimized structures of RuO₂ and Y-RuO₂ adsorbed with the intermediate are shown in Fig. 22. *OH Vo-site The intermediate refers to *OH adsorbed at vacancies after LOM. As shown in Fig. 21a, RuO₂ follows the AEM pathway (η AEM Compared to the LOM path (η) = 0.70 V) LOM It showed a much higher theoretical OER overpotential for (= 1.36 V), indicating a preference for the AEM path. In contrast, in Y-RuO₂, η LOM (0.52 V) becomes significantly lower compared to RuO₂, and η of Y-RuO₂ AEM It became lower than (0.81 V) (Fig. 21b). Therefore, introducing Y into RuO₂ makes the LOM pathway more favorable than the AEM pathway, which is a correlation consistent with the results observed in the DEMS analysis.

[0169] To identify the fundamental reason for this phenomenon, the p-band structure of O and the d-band structure of Ru were analyzed (Figs. 21c, 21d). Projected Density of States (PDOS) analysis revealed that Y-RuO₂ exhibited an upward shift of the O 2p band center and a downward shift of the Ru 4d band center compared to RuO₂, demonstrating enhanced Ru-O covalent bonding in Y-RuO₂. Furthermore, in Y-RuO₂, the O 2p valence band is closer to the Fermi level (EF) than the Ru 4d valence band, enabling it to participate actively in redox reactions. Taken together, these results confirm that in Y-RuO₂, lattice oxygen participates in the reaction, contributing to the enhancement of OER activity by shifting the OER mechanism from AEM to LOM. Additionally, changes in the O 2p band center and Ru-O covalent bonding following the introduction of other metal ions were examined and compared with OER activity (Figs. 21e, 21f). As a result, OER activity generally increased with the upshifting of the O 2p band center and the strengthening of Ru-O covalent bonding. Therefore, by controlling the OER mechanism as LOM through the downward shift of the Ru 4d band and the upward shift of the O 2p band to regulate Ru-O covalent bonding, it is possible to induce the participation of lattice oxygen in the anion redox reaction and develop an excellent OER electrocatalyst.

[0170] Finally, to verify the practical applicability of the LOM-based electrocatalyst developed in this study, the performance in a membrane-electrode assembly (MEA)-based PEMWE single cell was evaluated. When c-RuO₂ was applied to the PEMWE anode, the performance was 0.88 A cm⁻¹ at 1.6 V. -2 It was merely. In contrast, when Y-RuO₂ was applied to PEMWE, it was 1.39 A cm at 1.6 V. -2 It exhibited performance that was 1.58 times better than c-RuO₂ (Fig. 23a). Furthermore, at 1.81 V at 3 A cm -2By achieving the U.S. Department of Energy (DOE) 2026 technical performance target (3 A cm at 1.8 V) -2 It approached ). To analyze the differences in kinetic characteristics depending on the electrocatalyst, the Tafel slope was calculated using logarithmic graphs of overpotential and current density excluding high-frequency resistance (HFR). As a result, when Y-RuO₂ was applied, c-RuO₂ (142.4 mV dec -1 Lower Tafel slope (113.0 mV dec) than when applying -1 By showing ), it was confirmed that Y-RuO₂ enhances OER kinetics (Fig. 23b). Additionally, when the total overpotential was divided into activation overpotential, resistance overpotential, and mass transfer overpotential and compared, it was observed that in Y-RuO₂, not only was the activation overpotential reduced due to improved kinetics, but the mass transfer overpotential was also significantly reduced in the high current density region (Fig. 23c). This indicates an improvement in mass transfer characteristics attributed to the interparticle pores present in Y-RuO₂ synthesized using a ZIF template.

[0171] In practical applications, electrocatalytic durability can play a much more important role than activity. Therefore, for comparison, the durability of Y-RuO₂-based PEMWE as well as c-RuO₂-based PEMWE at 200 mA cm⁻¹ was -2It was evaluated in (Fig. 23d). During the 100-hour durability test, Y-RuO₂ maintained a stable voltage despite being a LOM-based electrocatalyst and showed less voltage increase compared to c-RuO₂. This result demonstrates that while c-RuO₂ follows AEM and Y-RuO₂ follows LOM to improve performance, Y-RuO₂ exhibits slightly better durability in a PEMWE single cell. This indicates that energy efficiency can be improved using LOM-based OER electrocatalysts even in acidic environments, while achieving durability similar to that of AEM-based OER electrocatalysts. This result challenges the conventional wisdom that inhibiting lattice oxygen activation in OER is necessary to improve PEMWE durability. Therefore, this opens a new path for the development of LOM-based OER electrocatalysts in acidic electrolytes.

[0173] conclusion

[0174] A major challenge in the practical application of PEMWE is to improve the durability of OER electrocatalysts while simultaneously enhancing their intrinsic kinetic activity. Although LOM-based electrocatalysts possess the potential to significantly improve intrinsic kinetic activity in OER without being constrained by linear relationships, they have been overlooked in acidic electrolytes due to their limited durability. In this study, we demonstrated that the introduction of d0 metal ions not only enhances OER activity by promoting the participation of lattice oxygen in the reaction but also contributes to the durability of LOM-based electrocatalysts. By utilizing the unique electronic properties of d0 metal ions to shift the center of the O 2p band upward and strengthen Ru-O covalent bonding, we successfully designed LOM-based electrocatalysts. The changes in the electrocatalyst's OER mechanism were verified through experimental implementations using DEMS and theoretical calculations using DFT. When implemented in PEMWE, the LOM-based electrocatalysts exhibited outstanding performance approaching the U.S. DOE's 2026 technology performance targets. At the same time, by challenging existing concepts and demonstrating superior durability, we confirmed the feasibility of applying LOM catalysts in PEMWE.

[0176] The foregoing description of the present invention is for illustrative purposes only, and those skilled in the art will understand that other specific forms can be easily modified without altering the technical spirit or essential features of the present invention. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive. For example, each component described as a single unit may be implemented in a distributed manner, and components described as distributed may likewise be implemented in a combined form.

[0177] The scope of the present invention is defined by the claims set forth below, and all modifications or variations derived from the meaning and scope of the claims and equivalent concepts thereof should be interpreted as being included within the scope of the present invention.

Claims

Claim 1 A catalyst for an oxygen evolution reaction comprising: a porous structure comprising ruthenium oxide (RuO2), wherein a plurality of ruthenium oxide primary particles aggregate to form secondary particles and include interparticle pores between the primary particles; and one or more metal ions having a d0 electron configuration dispersed on the surface or inside the pores of the porous structure; wherein the metal ions having a d0 electron configuration are one or more selected from the group consisting of Y (yttrium), Gd (gadolinium), and La (lanthanum), and wherein the area ratio (OV / OL) of oxygen vacancies (OV) to lattice oxygen (OL) in the O 1s spectrum measured by X-ray photoelectron spectroscopy (XPS) is 1.9 or higher. Claim 2 delete Claim 3 In paragraph 1, H₂ 18 Differential Electrochemical Mass Spectrometry coupled with isotope labeling experiments in 0.5 M H₂SO₄ electrolyte containing O A catalyst for an oxygen evolution reaction characterized by having a lattice oxygen participation rate of 30% or more in the oxygen evolution reaction (OER) as a result of DEMS. Claim 4 delete Claim 5 In claim 1, the specific surface area measured by the BET (Brunauer-Emmett-Teller) method is 40 m² 2 g -1 to 70 m 2 g -1 A catalyst for an oxygen evolution reaction characterized by being. Claim 6 In claim 1, 10 mA cm⁻¹ in a 0.5 M H₂SO₄ electrolyte -2 A catalyst for an oxygen evolution reaction characterized by the amount of Ru eluted into the electrolyte being 2.5 μg or less when operated at a current density of 10 hours. Claim 7 A catalyst for an oxygen evolution reaction according to claim 1, characterized in that the energy difference between the Ru 4d band center and the O 2p band center calculated by density functional theory (DFT) is 1.8 eV or less. Claim 8 A catalyst for an oxygen evolution reaction according to claim 1, characterized in that the center of the O 2p band is -3.4 eV or higher according to density functional theory (DFT) calculations. Claim 9 In claim 1, 10 mA cm⁻¹ in a 0.5 M H₂SO₄ electrolyte -2 A catalyst for an oxygen evolution reaction characterized by having an overvoltage of 250 mV or less for achieving a current density. Claim 10 In claim 1, the Tafel slope measured in a 0.5 M H₂SO₄ electrolyte is 40 mV dec -1 A catalyst for an oxygen generation reaction characterized by the following: Claim 11 A method for manufacturing a catalyst for an oxygen evolution reaction, comprising: a step of preparing a zeolitic imidazolate framework (ZIF) template; a step of contacting the ZIF template with an aqueous solution containing ruthenium ions and metal ions having a d0 electron configuration so that the ZIF template is gradually etched while simultaneously forming ruthenium and d0 metal precursors; and a step of heat-treating the ZIF template formed with ruthenium and d0 metal precursors in air to obtain a ruthenium oxide catalyst having a porous structure according to claim 1 into which the d0 metal ions are introduced. Claim 12 A method for manufacturing a catalyst for an oxygen generation reaction, characterized in that, in claim 11, the ZIF template is ZIF-8. Claim 13 A method for preparing a catalyst for an oxygen evolution reaction according to claim 11, characterized in that the precursor of the metal ion having the d0 electron configuration is in the form of a nitrate or a chloride. Claim 14 A method for manufacturing a catalyst for an oxygen evolution reaction according to claim 11, characterized in that the heat treatment step is performed in a temperature range of 300 °C to 400 °C. Claim 15 A method for manufacturing a catalyst for an oxygen evolution reaction according to claim 11, wherein the aqueous solution comprises ruthenium chloride (RuCl₃·xH₂O) and one or more dO metal salts selected from Y(NO₃)₂·6H₂O, Ce(NO₃)₂·6H₂O, La(NO₃)₂·6H₂O, or Gd(NO₃)₂·6H₂O, wherein the aqueous solution comprises the step of contacting the ZIF template with an aqueous solution containing ruthenium ions and metal ions having a dO electron configuration so that the ZIF template is gradually etched and ruthenium and dO metal precursors are formed simultaneously. Claim 16 A proton exchange membrane water electrolysis device comprising: an anode; a cathode; and a proton exchange membrane disposed between the anode and the cathode, wherein the anode comprises the catalyst of claim 1. Claim 17 In paragraph 16, the catalyst loading amount at the anode is 2.0 mgcat cm⁻¹ -2 Up to 4.0 mg cat cm -2 A proton exchange membrane water electrolysis device characterized by having a range. Claim 18 A proton exchange membrane water electrolysis device according to claim 16, characterized by being operated at an operating temperature of 80 °C to 100 °C. Claim 19 In paragraph 16, 1.0 A cm at a cell voltage of 1.6 V -2 A proton exchange membrane water electrolysis device characterized by exhibiting a current density above. Claim 20 In paragraph 16, 200 mA cm -2 A proton exchange membrane water electrolysis device characterized by a cell voltage rise of 20 mV or less when operated for 100 hours at a current density.

Citation Information

Patent Citations

  • Ruthenium-based oxygen evolution catalyst, preparation method and device

    CN118996520A

  • Cerium-tungsten co-doped ruthenium oxide catalyst capable of balancing lattice oxygen consumption and filling

    CN120505661A